Combination of osteogenesis imperfecta and type 1 diabetes mellitus - D. A. Marmalyuk; G. E. Runova; S. E. Moshenina; M. P. Shapka; V. V. Fadeyev (Сахарный диабет, 2022)
Osteogenesis imperfecta (OI) is a hereditary connective tissue disorder accompanied by increased bone fragility. Five types of OI are distinguished on the basis of phenotypic manifestations. OI type 1 is characterized by a reduced amount of normal type 1 collagen and is the mildest form. In addition to the fractures, course of disease can be accompanied by short stature, skeletal deformity and joint hypermobility. Although fracture risk decreases with age, such patients needs regular follow-up with an assessment of bone mineral density (BMD) and, if necessary, correction of therapy to improve the quality of life. Type 1 diabetes mellitus (T1DM) is associated with a decreased BMD, which is mostly attributed to insulin deficiency and hyperglycemia, which also increase the risk of fractures. Achieving and stable maintenance of glycemic targets is often challenging, but it is necessary to exclude hyperglycemia as a factor that further worsens the quality of bone. This paper describes a clinical case of an extremely rare combination of type 1 OI and T1DM, two diseases with a pronounced negative effect on bone tissue. The combination of these pathologies requires special management tactics for such patients to reduce the risk of developing new fractures.